Comparative morphology of pre-extrusion larvae, sebastes mentella and sebastes norvegicus (Pisces: Sebastidae) in Icelandic waters - Vergara, Alba Ruth; Sigurdsson, Thorsteinn; Saborido-Rey, Fran (Journal of Fish Biology, 2013)
12 páginas, 5 tablas, 3 figuras This study evaluated potential differences in morphology of unextruded larvae from Sebastes mentella and Sebastes norvegicus in Icelandic waters. Fifty-four larvae of each species were measured, and 18 measurements were recorded for each specimen (morphometric, meristic and pigmentation patterns). Pre-extrusion larvae of S. norvegicus were longer than those of S. mentella. Additionally, there were significant differences in morphometric, meristic and pigmentation characters between pre-extrusion larvae of these species. Pigmentation of S. mentella differed from that of S. norvegicus in several aspects. Dorsal and ventral body pigmentation tended to begin more posteriorly in S. mentella, therefore, the overall length of these pigmented areas tended to be longer in S. norvegicus. Funding for A.R.V. was provided by the Xunta de Galicia (Programa Isidro Parga Pondal) Peer reviewed